USAHA KESEJAHTERAAN ANAK TERKAIT KESEHATAN DI KAMPUNG NELAYAN CILINCING: Child Welfare Efforts Related to Health in the Cilincing Fisherman’s Village - Nabila, Farra Mutiara; Retnowulandari, Wahyuni (Faculty of Law, Universitas Trisakti, 2024)
Children's health has a significant impact on their growth and development. Every child has the right to receive welfare both in terms of health and growth and development, as stated in Article 2 paragraph (1) of Law Number 4 of 1979 concerning Child Welfare, which states,